1998
DOI: 10.1007/bf01450893
|View full text |Cite
|
Sign up to set email alerts
|

Primary vasculitis in a Norwegian community hospital: A retrospective study

Abstract: Primary systemic vasculitic diseases are relatively rare. Untreated, they have a high morbidity and mortality. The introduction of steroids and cytotoxic drugs has dramatically reduced the mortality. In a retrospective study in a Norwegian community hospital, which serves a county with a population of 150,426 in 1996, 68 patients were found to have a primary vasculitis, 63 of whom fulfilled the ACR 1990 criteria. Patients with Henoch-Schönlein purpura aged less than 16 years and patients with Kawasaki's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 22 publications
3
45
0
4
Order By: Relevance
“…However, CSS is a rare pathology, multisystemic, seldom taken care of exclusively in outpatient [8]. These results are also superimposable with other important European series (incidence: 1-4/million inhabitants/ annum within the general population [9][10][11][12] and prevalence: 2-13/million inhabitants [12][13][14]), confirming the absence of North-South or East-West gradient within this pathology [13] or evolution in time [11] contrary to other vasculitis as the disease of Wegener whose incidence is currently in increase and who has a North-South decreasing gradient [15].…”
Section: Discussionsupporting
confidence: 53%
“…However, CSS is a rare pathology, multisystemic, seldom taken care of exclusively in outpatient [8]. These results are also superimposable with other important European series (incidence: 1-4/million inhabitants/ annum within the general population [9][10][11][12] and prevalence: 2-13/million inhabitants [12][13][14]), confirming the absence of North-South or East-West gradient within this pathology [13] or evolution in time [11] contrary to other vasculitis as the disease of Wegener whose incidence is currently in increase and who has a North-South decreasing gradient [15].…”
Section: Discussionsupporting
confidence: 53%
“…In Germany during 1994, the prevalence of WG in the north and south of the country was reported to be 58 per million and 42 per million, respectively (3). A retrospective study from Norway in 1996 reported a WG prevalence of 53 per million (17). The highest reported prevalence figures to date come from Sweden where the prevalence of WG at the end of 2002 was 160 per million (18).…”
Section: Discussionmentioning
confidence: 99%
“…Either both of the systems or only the CHCC were used by most of the studies included in these analyses; 4 studies used only the ACR criteria (33,38,59,60). Although MPA is only clearly defined in the CHCC criteria, the incidence of WG in those studies that used only the ACR criteria are consistent with that at other similar (59,60) or lower (33) latitude locations. Indeed, for the latter, the incidence of both WG and MPA is considerably lower than other similar latitude sites.…”
Section: Association Between Uv Radiation and Wg Mpa And Cssmentioning
confidence: 99%